Strategic optimization of artificial intelligence for marketing communications in the creative industry - Faustyna Faustyna (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
Artificial intelligence (AI) has become an agent of change in marketing communication and in the creative industries. This study explores the growing role of AI in content personalization, marketing automation, and consumer data analysis. Beyond its various advantages, the application of AI can also be problematic, for instance, about data privacy and ethical concerns, as well as human-centered innovation, that influences creative thinking and practices across a range of domains. The objective of this paper is to explore how AI has influenced marketing communication strategies; to call attention to the most likely difficulties to be faced with its implementation in creative industries. From a qualitative approach, data were gathered from interviews with marketing professionals of innovative companies and by analyzing relevant documents. The findings demonstrate the potential for marketing AI based on automation, content customization, and real-time data analysis. However, the topics of data privacy, marrying technology with human creativity, and the necessity for a specific kind of training are still big hurdles. The findings indicate that firms need to integrate AI and creativity for constructing an efficient marketing strategy.